Biofungicida à base de derivados anfifílicos catiônicos de quitosana e método de obtenção do mesmo - Tiera, Marcio José [UNESP]; Tiera, Vera Aparecida de Oliveira [UNESP]; Gabriel, Juliana dos Santos; Pedro, Rafael de Oliveira (Instituto Nacional de Propriedade Industrial (INPI), 2014)
The present invention relates to biofungicides based on cationic, amphiphilic chitosan derivatives, with increasing proportions of dodecyl groups, for use against the fungus Aspergillus flavus, and to the method for producing said biofungicides.
Biofungicide based on cationic, amphiphilic chitosan derivatives and method for producing same
Processo: WO2014043774
Número de publicação: WO2014043774 (A1)
Número de aplicação: WO2013BR00356